The Effect of the Concentration of EM4 Addition on the Fermentation of Growing Media and Control of Environmental Temperature and Humidity on the Physical Characteristics of Oyster Mushrooms - Kawenuh, Wayan; Widia, I Wayan; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Increasing the yield of oyster mushrooms plays an important role to meet market demand and is expected to improve the welfare of farmers. This research was conducted to see the effect of the concentration of EM4 addition on the fermentation of the growing media as well as the control of environmental temperature and humidity on the physical characteristics of oyster mushrooms, and also the best interaction between the two treatments. The study used a factorial randomized block design with two treatment factors, namely the addition of EM4 (without EM4, 2, 4, 6, 8, and 10 mL/baglog) and temperature and humidity control (conventional and automatic controlled environment). Each treatment was made three times replication. The results showed that the addition of EM4 treatment and control of temperature and humidity had a significant effect on fresh fruit body weight and stalk length. The interaction of the addition of EM4 treatment and control of temperature and humidity significantly affected stalk length but did not affect the parameters of fresh fruit body weight, number of fruit bodies, hood diameter, and age of the first harvest. The addition of EM4 4 ml/baglog and controlled environment automatically is an interaction treatment that produces the best physical characteristics of oyster mushrooms. The physical characteristics produced were 125.8 g fresh fruit body weight, 21 fruit bodies, 6.92 cm hood diameter, 7.5 cm stalk length, and 24 days of the first harvest.